A kinetic study of baker's-yeast pyruvate kinase activated by fructose 1,6-diphosphate - Macfarlane, Neil (1972)
The paper reports a study of the kinetics of the reaction between phosphoenolpyruvate, ADP and Mg(2+) catalysed by yeast pyruvate kinase when activated by fructose 1,6-diphosphate and K(+). The experimental results indicate that the reaction mechanism is of the Ordered Tri Bi type with the substrates binding in the order phosphoenolpyruvate, ADP and Mg(2+). Direct phosphoryl transfer takes place in the quaternary complex, with pyruvate released before MgATP. A dead-end enzyme–pyruvate complex is also indicated. Values have been determined for the Michaelis, dissociation and inhibition constants of the reaction. Several of the rate constants involved have also been evaluated.